2015
DOI: 10.1111/ans.12973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of the pedicled anterolateral thigh flap in reconstruction

Abstract: Our experience has shown the wide arc of rotation, large skin replacement potential, multiple components and reliability of pedicled ALT flaps. They are technically simple to apply as myocutaneous/fasciocutaneous flaps with minimal donor site morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity . Li et al reported that pALT flaps have a lower recurrence rate but require a longer operative time and prolonged anaesthesia than hatchet‐shaped TFL flaps for the surgical management of trochanteric sores.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity . Li et al reported that pALT flaps have a lower recurrence rate but require a longer operative time and prolonged anaesthesia than hatchet‐shaped TFL flaps for the surgical management of trochanteric sores.…”
Section: Discussionmentioning
confidence: 97%
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity. 13,15,16 Li et al 17 reported that pALT flaps have a lower recurrence rate but require a longer FIGURE 2 An 83-year-old woman with multiple pressure sores. A, B, C, 12 cm × 16 cm sacral pressure sore, 8 cm × 5 cm right trochanteric pressure sore, and 3 cm × 3 cm left trochanteric pressure sore, respectively; D, left trochanteric pressure sores treated with delayed primary closure; E, right trochanteric defect covered with hatchet-shaped tensor fascia lata flap; F, planning of SGAP flap for sacrum defect; G, appearance of elevated f lap; and H, I, postoperative result 8 weeks after the surgery operative time and prolonged anaesthesia than hatchetshaped TFL flaps for the surgical management of trochanteric sores.…”
Section: Discussionmentioning
confidence: 99%
“…miR-181b-5p is carried in AT-MSC-derived EVs and enhances the mobility and angiogenesis of brain microvascular endothelial cells (BMECs) after oxygen-glucose deprivation by targeting transient receptor potential melastatin 7 (TRPM7) expression [63]. Several other miRNAs with angiogenic potential such as miRNA-494, miR-125a, or miR-210 were recently reported in MSC-derived EVs [64][65][66].…”
Section: Ev-associatedmentioning
confidence: 99%
“…Many authors focussed the utility of pedicled ALT for various soft tissue defects pertaining to specific anatomical regions [4][5][6][7]. To the best of our knowledge, very few articles described the diverse anatomical locations where pedicled ALT flap was used, including the abdomen, groin, trochanteric region, and the knee [8].…”
Section: Discussionmentioning
confidence: 99%